2019
DOI: 10.15560/15.6.1107
|View full text |Cite
|
Sign up to set email alerts
|

Found in Brazil again! Expanding the distribution of Maxillaria aureoglobula Christenson (Orchidaceae, Maxillariinae) and a key to the species of Maxillaria sect. Rufescens Christenson from Brazil

Abstract: The distribution of Maxillaria aureoglobula is expanded to northeastern Brazil. This species is probably more geographically widespread than expected, and the new record reported here is a geographical link between the other occurrences of this species in northwestern South America (Colombia and Venezuela) and a recent record from Mato Grosso in the Brazilian Central-West Region. We provide an expanded description of the species, a distribution map, and a key to the Brazilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Various recent floristic studies confirm that Maranhão is undercollected (Ferreira et al 2017, Ferreira et al 2018, Ferreira et al 2019a, b, Ferreira et al 2022, Gomes et al 2021, Guarçoni et al 2018a, b, Guarçoni et al 2020, Oliveira et al 2021, Scatigna et al 2020. There are few surveys of the fern and lycophyte species in Maranhão (Almeida et al 2020, Silva Junior et al 2020, Fernandes et al 2022, suggesting the need for new botanical studies in the state to update the Flora e Funga do Brasil database, which currently only lists five Selaginella species.…”
Section: Discussionmentioning
confidence: 99%
“…Various recent floristic studies confirm that Maranhão is undercollected (Ferreira et al 2017, Ferreira et al 2018, Ferreira et al 2019a, b, Ferreira et al 2022, Gomes et al 2021, Guarçoni et al 2018a, b, Guarçoni et al 2020, Oliveira et al 2021, Scatigna et al 2020. There are few surveys of the fern and lycophyte species in Maranhão (Almeida et al 2020, Silva Junior et al 2020, Fernandes et al 2022, suggesting the need for new botanical studies in the state to update the Flora e Funga do Brasil database, which currently only lists five Selaginella species.…”
Section: Discussionmentioning
confidence: 99%
“…Encyclia gonzalezii bloomed under cultivation between October and November, a time similar to the flowering period mentioned by Meneguzzo et al (2012), i.e., between September and October. Despite the botanical potential of Maranhão, not much research is available about surveying species. Recent studies in Maranhão have shown that, with increasing sampling effort, new records of Orchidaceae (Ferreira et al 2017(Ferreira et al , 2019aGomes et al 2021;Oliveira et al 2021;Pessoa et al in press) and other plant families (Ferreira et al , 2019bGuarçoni et al 2020b;Silva Júnior et al 2020) are discoverable. Even new species are found in Maranhão, as attested by Scatigna et al (2019), Guarçoni et al (2020a), andSantos et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, M. sect Rufescens is represented by three native species: M. aureoglobula Christenson (2002b, p. 125) (Brazil west-central and northwest of South America); M. cleistogama Brieger and Illg in Illg (1977, p. 247) (Bolivia, Brazil, Peru and Venezuela), and M. rufescens Lindley (1836Lindley ( , t. 1848) (widespread in South and Central America) (Engels and Ferneda Rocha 2016, Marcusso et al 2018, Ferreira et al 2019, Meneguzzo et al 2020, , POWO 2022. The present study describes a fourth species from the oriental Brazilian Amazon.…”
Section: Introductionmentioning
confidence: 99%